The Returns to Elite Degrees: The Case of American Lawyers. (March 2019) - Oyer, Paul; Schaefer, Scott
The authors study the market for young attorneys. Using data from two surveys of attorneys who passed the bar exam in 2000, they find that attorneys who graduate from law schools ranked in the Top 10 nationally earn considerably more than those without such a qualification, even compared to attorneys who graduate from schools ranked 11–20. The premium to an elite education carries over to an attorney's undergraduate institution as well, and the findings suggest that elite bachelor's degrees and elite law degrees are close substitutes in terms of their relationships to salaries. The elite–law school premium is more robust to various methods for correcting for selection on ability than the widely studied premium to attending a selective undergraduate institution. The authors consider several reasons elite-school premiums may exist in this labor market.